Al-Sulṭānah fī Cirebon: Dirāsah Tārīkhīyah wa Thaqāfīyah - Uka Tjandrasasmita (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This article discusses the Sultanate of Cirebon from two perspectives. First, from its historical standpoints, including its rise, development and fall. Second, from its cultural point of views covering such aspects as architecture, literature, and performing arts, which have become local traditions until nowadays. Geographically, Cirebon is located in Northern part of law coast. Its strategic location, with a number of river mouths, plays an important role for the development of Cirebon to become a harbor city for regional and international sailing and trading nativities. The position of Cirebon as a harbor city has begun since Hindu and Buddhist Kingdom of Sundanese Pajajaran, as can be seen from local archives, such as babad and carita, as well as foreign historical records.DOI: 10.15408/sdi.v16i2.485